PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE NOVAGE PADA PT ORINDO ALAM AYU (ORIFLAME SWEDAN) MEDAN - Jesika Lusiana Siregar; Purnama Yanti Purba; Demak Claudia Yosephine Simanjuntak; Rudi Halim; Jackson Tanama (Jurnal Akrab Juara, 2019)
This research aims to know and analyze the effect of the price and promotion to purchasing decision of SkinCare Novage in PT Ayu (Oriflame Swedan) Medan. The phenomenon of instability SkinCare Novage product caused by the high price and stagnant promotional motivate researcher to do this research. Analysis Methods of this research is multiple linear regression analysis. The technique of sample determination is simple random sampling. The results of the analysis found that the promotion affects buying decision most dominant. This is proved by the results of the calculation hypotheses on t- test and f-test. The results showed that either price or the promotion effects purchasing decision of SkinCare Novage partially and significantly on PT Orindo Alam Ayu (Oriflame Swedan) Medan. Price and promotion are also effect purchasing decision of SkinCare Novage simultaneously on PT Orindo Alam Ayu (Oriflame Swedan) Medan